Periodontitis and risk of stroke: a systematic review and meta-analysis of observational studies - Meng, Xinyu; Chen, Xiaohua (Frontiers in Neurology, 2025)
ObjectivesTo evaluate whether periodontitis is associated with stroke and to update pooled estimates with recent studies.MethodsWe systematically searched Medline, Embase, and the Cochrane Database of Systematic Reviews from inception to July 2025. We included cohort and case–control studies of adults comparing periodontitis with no periodontitis and reporting any stroke (ischemic, hemorrhagic, or unspecified). Random-effects models were used. Case–control and cohort data were pooled separately. Prespecified subgroups included stroke subtype, study design, sex, and follow-up duration. Publication bias was assessed when ≥10 studies were available.ResultsTwenty-two studies were included (16 cohorts; 6 case–control). In case–control studies, periodontitis was associated with higher odds of stroke (OR, 2.22; 95% CI, 1.48–3.34; I2 = 33%). In cohorts, periodontitis was associated with increased incident stroke risk (RR, 1.49; 95% CI, 1.23–1.80; I2 = 96%). In subgroup analysis, prospective cohorts showed slightly higher and more stable estimates than retrospective cohorts (RR, 1.53 vs. 1.40; I2 = 61% vs. 98%). Studies with >10 years of follow-up showed a stronger, less heterogeneous association (RR, 1.57; 95% CI, 1.35–1.84; I2 = 32%). Funnel plots suggested limited publication bias.ConclusionsPeriodontitis is associated with increased stroke risk, most clearly for ischemic outcomes and in long-term prospective cohorts. Given high heterogeneity and potential residual confounding, the findings support association rather than causation. Standardized periodontal definitions, subtype-specific endpoints, and rigorous prospective and interventional studies are needed to test clinical impact.